The role of institution on corn-based food diversification in Konawe District, Southeast Sulawesi. Issue 1 (February 2020) - Tamburaka, I P; Tajuddin,; Apoda,
Abstract: This study aims to determine the institutional role of corn-based food diversification in Konawe Regency. This research was conducted in several areas of corn production centres in Konawe District, Consideration of location selection was determined based on the criteria of the largest corn production centre and marketing centres. The number of respondents determined purposively each location, the total number of 80 respondents. Types and sources of data are secondary data and primary data. Qualitative analysis is used to explore the role of community organizations in the application of corn-based food diversification research results to social capital theory. Community group organizations are represented by farmer groups and PKK (family welfare empowering) women groups. The existence of social capital in the two groups is approached through understanding their mindset and actions in every activity carried out in the group. The results of the study concluded that the role of institutions (farmer groups and women's PKK) on maize processing as an alternative to rice needs to be improved through counselling and assistance from relevant agencies.